Spectrophotometric and Liquid Chromatographic Determination of Dopamine from Pharmaceutical Preparations Using 2-Hydroxynaphthaldehyde as Derivatizing Reagent - RAJPER, A.D.; ARAIN, G.M.; RIND, F.M.A.; KHUHAWAR, M.Y. (Asian Journal of Chemistry, 2010)
Dopamine has been determined by spectrophotometry and liquid chromatography as derivative of 2-hydroxynaphthaldehyde. The optimal derivatization occurred at pH 8 with enhancement in spectrophotometric sensitivity. The spectrophotometry was used for the analysis of dopamine in pharmaceutical preparations. The liquid chromatography of dopamine was carried out in the presence of 4-aminobutyric acid and tyramine. The separation was obtained from Phenomenex C-18 column 5 μm (150 × 4.6 mm id) by isocratic elution with methanol:acetonitrile: water (54:4:42 v/v/v) with a flow rate of 1.2 mL min-1, UV detection was at 330nm. Linear calibration curves were obtained for each within 0.33-40.00 μgmL-1 with detection limits in the range 1.9-8.2 ng injection-1 (10 μL). The dopamine was determined in pharmaceutical preparations with coefficient of variation within 0.8-2.5 %.